2016
DOI: 10.1097/md.0000000000005470
|View full text |Cite
|
Sign up to set email alerts
|

Could ADC values be a promising diagnostic criterion for differentiating malignant and benign hepatic lesions in Asian populations

Abstract: Background:Liver cancer exhibits geographic and ethnic differences in its prevalence and biology, which implies that it is impractical to develop universal guidelines for all patients. Thus, a meta-analysis was conducted to identify the accuracy of apparent diffusion coefficients (ADCs) for discriminating malignant from benign liver lesions in Asians.Methods:Eligible studies published in PubMed, Ovid, and Embase/Medline were updated onto October 2014. STATA 12.0 and Meta-Disc 1.4 were used to perform this meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 61 publications
(58 reference statements)
1
5
0
Order By: Relevance
“…[29] The reason for this wide range may be the application of different DWI sequence parameters such as different b values and use or non-use of a parallel imaging technique. [15] In our study, we used a high b value, and as a result of this, we found an average ADC value for metastases close to the lower limit in the literature. In a large number of studies, ADC values of metastases were found to be lower than those of HCC, [9,10,13,14,18,19] while ADC values of metastases were found to be higher than those of HCC in several other studies.…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations
“…[29] The reason for this wide range may be the application of different DWI sequence parameters such as different b values and use or non-use of a parallel imaging technique. [15] In our study, we used a high b value, and as a result of this, we found an average ADC value for metastases close to the lower limit in the literature. In a large number of studies, ADC values of metastases were found to be lower than those of HCC, [9,10,13,14,18,19] while ADC values of metastases were found to be higher than those of HCC in several other studies.…”
Section: Discussionsupporting
confidence: 53%
“…In the literature, there are several studies investigating ADC values of focal liver masses. [9][10][11][12][13][14][15][16][17][18][19] In these studies, ADC values in benign lesions were found to be higher than those of malignant lesions. [9][10][11][12][13][14][15][16][17][18][19] However, there are overlaps of ADC values in both benign and malignant lesions.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…It has been already reliably proved that many malignant tumors, as well as their metastases, show noticeable restricted diffusion, which is being taken into consideration in routine clinical daily practice as an additional tool in differential diagnosis and even grading malignancy, discriminating disease stages, predicting response to treatment, differentiating recurrence or residual mass from post-treatment changes [12][13][14][15][16][17][18][19].…”
Section: Discussionmentioning
confidence: 99%